New Xanthene Diones Compounds as a Corrosion Inhibitor of Mild Steel in Acid Medium: Electrochemical, Surface Characterization and Theoretical Insights - Dahmani, K.; Galai, Mouhsine; Ouakki, M.; Benzekri, Z.; El Magri, A.; Iachhab, R.; Cherkaoui, M. (Springernature, 2023)
Two newly synthesized inhibitors, namely 3,3,6,6-tetramethyl-9-phenyl-3,4,6,7-tetrahydro-2H-xanthenes-1,8 (5H,9H)-dione (ZM-3) and 9-(4-Bromophenyl)-3,3,6,6-tetramethl-3,4,5,6,7,9-hexahydro-2H-xanthene-1,8-dine (ZM-4) have been reported in the current study as a promising corrosion inhibitors of mild steel (MS) in 1 M HCl solution. Electrochemical experiments such as Electrochemical Impedance Spectroscopy (EIS) and Potentiodynamic Polarization measurements (PP) were performed for this aim. The quantum properties of the molecules were also calculated and analyzed using theoretical chemistry principles. Density Functional Theory was used in order to achieve this (DFT). The inhibitory action mechanism was discovered using Molecular Dynamic Simulation (MDS). The increase of the inhibitor concentration was thought to have resulted in a considerable reduction in MS corrosion rate in molar hydrochloric acid solution, with inhibitive efficiency values of 90.8 and 91.3% at 10(-3) M inhibitor concentrations of ZM-3 and ZM-4, respectively. As the inhibitor concentration was increased, the inhibition effectiveness improved. Using temperatures ranging from 298 to 328 K, the effect of temperature on the corrosion behavior of MS in molar HCl at the inhibitor's optimum concentration of 10(-3) was investigated. ZM-3 and ZM-4 behaved as mixed type inhibitors, according to polarization plots. The Langmuir isotherm model fit the adsorption mechanism of the evaluated inhibitors. Scanning Electron Microscopy with Energy Dispersive X-Ray Analysis (SEM/EDX), Atomic force microscopy (AFM), contact angle, and X-ray Powder Diffraction (XRD) methods were used to examine the corroded surface.
Keywords: Xanthene diones; Corrosion inhibition; Mild steel; Electrochemical investigations; Computational calculations